Effect of magnetic field on quantum dot semiconductor laser - Safa Mahmoud Najm (Genius Journals, 2024)
The quantum dot laser is the latest generation in a series of laser developments in general and semiconductors in particular. As long as this laser has become widely available, its application importance has increased in various fields such as communications. Semiconductor lasers differ from ordinary solid-state lasers in the method of pumping energy and in containing broad bands of energy levels instead of single levels between which transitions occur that participate in the emission process. Laser, where each beam contains a large number of close energy levels whose presence is not associated with specific atoms, but rather is shared by the crystalline material, and the increase in the value of the optical gain factor is related to the amount of current that passes through the link of the semiconducting medium. A semiconductor laser is a laser made of a semiconductor material characterized by a direct bandgap. The most common type is a calcium arsenide diode, which emits infrared rays with a wavelength of 0.85 microns
Keywords: Magnetic fields; lasers; semiconductors; quantum dots